Socio-economic burden of Rift Valley fever outbreak in a pastoralist community in Marsabit County, Kenya, 2018 - Mathew Munyamaara Mutiiria; Peter Gatongi; Elvis Oyugis; Mathew Muturi; Athman Mwatondo; Bernard Chege; Juster Mungiiria (Journal of Interventional Epidemiology and Public Health)
Introduction: Rift Valley Fever (RFV) is an acute vector-borne viral zoonotic notifiable disease primarily of domestic animals. It causes significant economic impacts among livestock producers and consumers. An outbreak of RVF occurred in May-June 2018; Marsabit reported positive cases in humans and animals. The study described herd owners’ social demographic characteristics, estimated livestock mortality and quantified the direct and indirect monetary losses in Laisamis Sub-County. Methods: We conducted a cross-sectional study. Data was collected from 384 households. Direct and indirect costs were estimated using the economic model as described in Velthuis et al. (2008). Descriptive statistics were used to describe social-demographic characteristics. Economic burden incurred was the outcome variable. Results: Majority of the respondents were females (67.2%). Total direct and indirect economic burden/losses were 1,970,000 USD, cattle recorded the highest financial loss at 42.3% (832,850 USD) through mortality. Stormy abortions were the most common syndrome reported at 382(99%).No routine livestock vaccination against RVF. Young herd owners were more likely to suffer economic losses compared to the aged (>60 years of age). Male herd owners and those with formal education were less likely to experience financial loss at (OR=0.42, p-value < 0.0001) than female herd owners. Conclusion: A higher economic burden was associated with the RVF outbreak in Laisamis, particularly among female-headed households of younger age groups. Men had less odds of experiencing a financial burden compared to women. There is a need to vaccinate animals against RVF at the local level to reduce economic losses associated with an outbreak.